Experiences of Elderly Residential Care Transitions: a Review of Literature - Charenkova, Jūratė (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] Relocation to residential care facility in older age is considered as one of the most significant life transitions, that causes great deal of stress, depression and anxiety to the elderly. It is said, that transition to residential care facility is only slightly less stressful event than divorce or death of a spouse. After relocation older people are faced with a lot of unknowns in form of new people, new physical surroundings and new social demands. Relocation to residential care facility is a challenge for usual lifestyle: changes in one’s social network, loss of autonomy, reduced opportunities of maintaining favorite activities, adapting to new social and physical environment, attempts to create new home in residential care facility demand a lot of adaptive efforts from the elderly. These are the most common challenges to identity and well-being of the elderly. On other hand, relocation to residential care facility not only creates new challenges for elderly people, but also creates a new opportunities in form of new friends, new activities and sense of security since in case of emergency there are always staff close by. So there are possibilities of reconstructing one’s identity and maintaining well-being.